The scientific and ethical evaluation of a method [or the diagnostic sampling of human seminal fluid - Spagnolo, A. G.; Mancini, A.; De Marinis, L.; Chiarenza, D.; Le Pera, C.; Di Pietro, M. L.; Giacchi, E.; Pompa, G. (Medicina e Morale, 1993)
Many clinical situations require the sampling of seminai fluid for diagnostic reasons. lt is usually obtained through masturbation, but this collection method raises psychological and ethical objections. The article illustrates the results of a study carried aut on a small number of patients, who underwent sperm sampling with a special clinical vibrator. The results seem encouraging to authors and they conclude that, even though the number of cases was intentionally small, and a study is to be carried aut on a larger number of patients, the vibrator might be a valid alternative to masturbation, not only in Catholic hospitals, but in ali the health structures where seminai fluid is drawn, in order to provide an alternative to masturbation for people who are sensitive to the psychological and ethical problems that this diagnostic test can raise.